2013
DOI: 10.3390/rs5115725
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Parameters for Growing Stock Volume Estimation Using ALOS PALSAR L-Band Data over Siberian Forests

Abstract: Abstract:In order to assess the potentiality of ALOS L-band fully polarimetric radar data for forestry applications, we investigated a four-component decomposition method to characterize the polarization response of Siberian forest. The decomposition powers of surface scattering, double-bounce and volume scattering, derived with and without rotation of coherency matrix, were compared with Growing Stock Volume (GSV). To compensate for topographic effects an adaptive rotation of the coherency matrix was accompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…One good candidate parameter is HV-backscatter widely used for assessment of forest biomass [65,66], as it is highly correlated to forest stem volume. Another representative PolSAR parameter we adopt is polarimetric coherence investigated in several earlier studies [42,43]. Another rationale for such choice is incorporating two PolSAR parameters with distinctly different dependence on stem volume, into the stem volume prediction.…”
Section: Temporal Dependence Of Polsar Parameters and Relation To Stementioning
confidence: 99%
See 1 more Smart Citation
“…One good candidate parameter is HV-backscatter widely used for assessment of forest biomass [65,66], as it is highly correlated to forest stem volume. Another representative PolSAR parameter we adopt is polarimetric coherence investigated in several earlier studies [42,43]. Another rationale for such choice is incorporating two PolSAR parameters with distinctly different dependence on stem volume, into the stem volume prediction.…”
Section: Temporal Dependence Of Polsar Parameters and Relation To Stementioning
confidence: 99%
“…Another problem is suboptimal inversion scenario in model-based approaches, which may complicate routine stem volume estimation due to non-physical, negative or unrealistically high estimates of AGB, as discussed in [39]. Chowdhury et al used PolSAR variables in linear regression fitting [43] and polarimetric coherence in semi-empirical model inversion [42] to recover growing stock volume of Siberian forests. Results were encouraging with up to 33 m 3 /ha RMSE.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, synthetic aperture radar (SAR) data coupled with quad-polarimetric techniques have a stronger ability to account for the propagation and scattering mechanism than the single polarimetric SAR images [6]. With the capacity to penetrate forest canopies and interact with forest structures, quad-polarimetric SAR images provide great potential to improve the accuracy of forest GSV monitoring and assessment [6][7][8][9].Polarimetric characteristics that are highly sensitive to forest GSV can be used to accurately estimate forest GSV [6][7][8]10,11]. There are three kinds of polarimetric characteristics associated with forest GSV.…”
mentioning
confidence: 99%
“…There are three kinds of polarimetric characteristics associated with forest GSV. The first one is the trio of backscattering coefficients-horizontal-horizontal (HH), horizontal-vertical (HV) and vertical-vertical (VV) [7,8,12,13]. The backscattering coefficients of the dual and quad-polarization SAR images have been proved to be appropriate for estimating forest GSV [7,8,[11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Kwok et al [11] demonstrated the usability of the co-and cross-polarization signature for characterizing changes in the relative scattering contributions in the radar signal between frozen and thawed conditions. Recently, several studies applied polarimetric processing techniques to characterize wetland classes in Canada [16] and to estimate the growing stock volume in Siberian forest [21,22].…”
Section: Introductionmentioning
confidence: 99%